Technology dependent child: unveiling the reality of the family caregiver - Muriel Fernanda de Lima; Guilherme Oliveira de Arruda; Jéssica Batistela Vicente; Sonia Silva Marcon; Ieda Harumi Higarashi (Rev Rene)
This is a descriptive study, with a qualitative approach, with the purpose of comprehending the process of taking care of a technology dependent child, from the perspective of the preferential family caregiver and outlines the strengths and weaknesses of the family within the care process. Semi-structured interviews were conducted with nine family members living in Maringá, Paraná, Brazil in the first half of 2012. Data were analyzed based on Analysis of Content, thematic mode. It was identified that care is centered on the figure of the mother, who goes through a continuous process of learning, struggling with feelings such as fear and insecurity regarding care giving. The process of care imposed changes in the family routine and highlighted the need and importance of the support of the healthcare team to guide and clarify the doubts as well as the adoption of other coping strategies of this new routine.